El debate en torno al método historiográfico en el Chile del siglo XIX - Dager Alva, Joseph (Revista Complutense de Historia de América, 2002)
Tailored historiography in rising Hispano-American countries of the XIX century had the commitment to contribute to the «imagination» of nation, reason why it could not exactly fulfill the model of total absence of subjectivity, if some type of history can do it, although in general it repudiated philosophical speculation. This work focuses on the debate carried out in Chile in 1844 and 1848 about the suitable method to investigate the past. Andres Bello defended narrative history or ad narrandum, while the young Jose V. Lastarria and Jacinto Chacon advocated ad probandum or philosophical history as the suitable system to find historical truth. Towards the end, we offer a reflection on the influence of Bello’s lessons, through the analysis on the historical discipline notions used by Diego Barros Arana and Valentin Letelier.
Keywords: Chile XIX century; Andres Bello; Jose V; Lastarria; historiographyc debate; narrative history; philosophical history